Efeito da aplicação tópica de dipirona gel na redução da sensibilidade dental causada pelo clareamento de consultório : estudo clínico randomizado, controlado, triplo cego e multicêntrico - Vaez, Savil Costa (2018)
Introduction: Despite to present adequate clinical effectiveness on obtaining satisfactory color, the tooth sensitivity (TS) is usually reported by patients during and after the in-office dental bleaching. Thus, this study evaluated the effectiveness of topical application of sodium dipyrone when compared to placebo on risk and level of TS caused by dental bleaching. Methods: This was a randomized, controlled, triple-blinded, split-mouth clinical trial with 120 participants allocated in three research centers. The participants received topical application of dipyrone gel or placebo (one treatment per side of upper arch) 10 minutes prior to application of 35% hydrogen peroxide (two sessions) for 45 minutes (3 x 15 minutes). TS was recorded using two pain scales: visual analogue scale – VAS (0-10 cm) and verbal rate scale (0-4) during and until 48h after the bleaching procedures. The tooth color changes assessment was performed on month after the last bleaching session using two visual scales (Vita Classical e Vita Bleachedguide 3D-Master) and a portable spectrophotometer (Easyshade). For the verbal rate scale, data from risk and level of TS were analyzed by McNemar and Wilcoxon tests, respectively. Data for VAS were submitted to one-way ANOVA and T-test, which was also used to compare color changes between the treatments (α = 0.05). Results: The application of dipyrone did not affect the risk to TS (p = 0.092). There was no significant difference regarding the level of TS for all assessment times, except for one-hour post-bleaching using verbal rate (p = 0.02). It was observed bleaching effect of approximately four shade guide units and ΔE of six units, irrespective the prior treatment. Conclusion: The preemptive application of dipyrone did not affect the risk and level of TS caused by in-office dental bleaching.